(untitled) (Ius Novum, 2018)
The tourism services agreement is one of the most common contract on the market of tourism services, which basically comprehensively regulates the relationship between the participant of tourism event (the consumer) and professional entity (the tour operator). Proper stimulation of the relationship between professional and non-professional entities should therefore be the priority tasks of tourism policy, which can be achieved by using a wide catalog of instruments, including legal acts. Problems in the proper functioning of the agreement causes dysfunctions, which, due to the universality of the agreement, can create far-reaching negative effects. Of course, with no doubt, the content of the tourism services contract is one of the most important elements constituting the quality of the agreement on the market of tourism services. That is why, studies made concentrate on the issue of contractual information (the information contained in the contract), because it is reasonable to indicate that the professional entities ‘communicate’ with consumers also by using the content of the agreement, which includes basic information about the services and therefore consumers should pay special attention to the analysis of that content. It is more than obvious that the lack of equivalence between professional and non-professional entitles can be considered as the market defect, and hence can create far-reaching distortion of competition. Defects appearance often depends on the internal characteristics of the market. Therefore, firstly the identification of the main characteristics of the tourism market (created by the specificity of tourism products) will be done. Then, the detail issues related to professional entitles information duties with special emphasis on the content of the tourism services agreement will be discussed. The main considerations are divided into two areas: (1) remarks on the Directive 90/314 and the Tourism Services Act from 1997; (2) remarks on the Directive 2015/2302 and the proposal of new regulations (bill) on tourism events and linked travel arrangement.